PELATIHAN APOTEKER CILIK (ApoCil) DAN PENGENALAN DAGUSIBU DI MADRASAH IBTIDAIYAH NUR IKHLAS KECAMATAN TUALANG - Yan Hendrika; Vonny Kurnia Utama; Yulia Febrianita; Syamsul Bahri Riva’I (LPPM Universitas Abdurrab, 2022)
Pharmacists play a crucial role in the health sector as one of the professions, especially when it comes to drug education. One of the pharmacist's responsibilities is to promote the pharmacy profession and healthy drug usage from a young age. The fifth-grade children at MI Nur Ikhlas receive this service using socialization and educational techniques as well as instructional materials. The information delivered took the form of a summary of the pharmacy field and DaGuSiBu topics. This activity seeks to present pharmacists as health professionals and as a source of knowledge regarding the use of suitable medications to improve health status. The results of this service show that students are very enthusiastic and active in participating in activities, resulting in a change in students' knowledge about drug use. This type of education must be expanded to include more participants from various schools so that an increasing number of elementary school students understand how to use drugs rationally.